Analysis of Selected Heavy Metals in Surface Water and Sediments from Unreclaimed Mining Ponds Used for Irrigation Farming in Jos South, Nigeria (Ghana Journal of Science, Technology and Development, 2022)
The present study is aimed at examining the heavy metal contamination in surface water and sediments from selected unreclaimed mining ponds Bukuru and Rayfield towns, Jos south Local Government Area â€œL.G.Aâ€ Plateau State. Five representative unreclaimed ponds were purposively selected in each unreclaimed mine ponds of Bukuru and Rayfield. Water and sediment samples were collected from Januaryto September, 2019, with January to March representing dry season and April to September as rainy season. A total of 22 water samples were collected for the study with 11 samples in each of the seasons. Samples collected for each of the seasons were analyzed for Cd, Mn, Hg, Cu, Ni, Pb, Ur and Zn, while a control point was selected in Riyom. In the exception of Cd, mean levels of sampled metals were within NESREA permissible limits in water samples for most locations, while Mn, Hg Cu were very high and above permissible limits. The result of a one-sample t-test showed that there is no significant difference between the observed mean levels and NESREA standard either in water at p>0.05, d = 0.0993 or sediment at p>0.05, d = 0.209. Mean levels of all heavy metals in both water and sediment samples were higher in the dry season when compared to the rainy season samples, although the difference was not statistically significant at p>0.05, d = 0.052 for water, while the difference was found in sediment at p>0.05, d = 0.015. The study found that concentration levels in sediment were significantly higher than levels in water at p>0.05, d = 0.006. In terms of spatial variation, concentration levels differ significantly in sediment samples between Bukuru and Rayfield mine sites at p>0.05, d = 0.019, while water samples did not show a statistical difference at p>0.05, d = 0.053 between the two locations. Since the water in unreclaimed mining ponds are used for fish farming, irrigating and domestic purposes, it is of great concern that Cd is in high concentration because it is extremely toxic and carcinogenic.